Bleeding and thrombosis in intensive care patients with thrombocytopenia—Protocol for a topical systematic review. Issue 2 (14th October 2018) - Jonsson, Andreas Bender; Rygård, Sofie Louise; Russell, Lene; Perner, Anders; Møller, Morten Hylander
Abstract : Background: Thrombocytopenia is a common condition in critically ill patients in the intensive care unit (ICU). It is associated with prolonged stay in the ICU, increased transfusion requirements, risk of bleeding and mortality. The evidence regarding the use of prophylactic platelet transfusion and thrombosis prophylaxis in patients with thrombocytopenia in the ICU is unknown. To direct future research, we aim to assess the current evidence regarding prophylactic platelet transfusion and thrombosis prophylaxis on patient‐important benefits and harms in the ICU population. Methods: We will conduct a topical systematic review of all study designs (ie no study design will per se be excluded from the proposed review) in accordance with the Preferred Reporting Items for Systematic and Meta‐Analyses (PRISMA) statements. We will include studies on adult patients in the ICU where the incidence of thrombocytopenia and the predefined outcome measures, including mortality, quality‐of‐life, thrombotic events and haemorrhagic events are reported. We will provide descriptive analyses of the included studies/trials, ie no meta‐analyses will be conducted, and the quality of evidence will be assessed according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Conclusion: The outlined topical systematic review will provide important data on the benefits and harms of prophylactic platelet transfusion and thrombosis prophylaxis in ICU patients with thrombocytopenia and provide estimates on the rate of thrombocytopenia in this vulnerable population.